Classification of Skin Color Detection System to Determine Color Selection in Cosmetics (Foundation) Using Modified Chamfer Matching Algorithm Method - Dadang Iskandar Mulyana; Indah Rosmalina (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2025)
Skin color detectionis one of the segmentation processes that separates object regions in an image based on color differences. Objects that have a certain color are separated from objects that have other colors. The segmentation results can be used for further processes such as feature extraction or image classification. In this example, skin color is defined in the YCbCr color space with a Cb value between 77 and 127 and a Cr value between 133 and 173. Skin color detection is one of the initial stages in computer vision to detect things related to humans (people detection). Skin color detection can be used as a segmentation method for face recognition or recognition of other body organs. The system can be further developed for biometric systems.